Comparison of Speed Completion System Linear Equations Using the Elimination Method and Using Arithmetic Sequences - Zunaida Sitorus; Miftahul Jannah; Nurliana Nurliana; Septi Nur Selase (Journal of Education and Teaching Learning, 2023)
There are many ways to solve linear system equation problems, such as using Gaussian Elimination or the elimination method. To solve linear system equation problems, we can transform them into an arithmetic sequence. This method can make it easier to answer the questions quickly. The objective of this research is to provide a comparison of problem-solving using the elimination method and using arithmetic sequences. The method used in this research is quantitative. Data collection involves solving linear system equation problems and recording the time it takes to solve them using both the elimination method and the arithmetic sequence method. The data used consists of UNBK (National Computer-Based Exam) questions and university selection questions, comparing the time it takes to solve problems using the substitution method and the arithmetic sequence method. The conclusion from this research is that the use of arithmetic sequences in solving linear equations is easier and faster, making it applicable when answering exams with limited time duration.